The Value of Photography in Vocabulary Acquisition in a Language Treatment Program - Cortellino, Rachel (My University, 2010)
The purpose of this investigation was to determine the relationship between the use of photography and vocabulary acquisition. Specifically, it was designed to look at the responses photographs elicited as compared to responses that traditional therapy materials, such as the use of representational flash cards, elicited. The investigation also looked at reinforcement and subject involvement in therapy. The results indicated that the value of photographs had no initial impact but in post treatment had an apparent residual effect. Implications and recommendations are presented.
Keywords: Photography; Vocabulary; Communication Sciences